Adaptive threshold QRS detector with best channel selection based on a noise rating system - Emmanouilidou, Dimitra (Computing in Cardiology Conference, 2007)
QRS detection performance can depend on the type of noise present in each lead involved in the overall processing. A common approach to QRS detection is based on a QRS enhanced signal obtained from the derivatives of the pre-filtered leads. However, the signal pre-filtering cannot be able to perform a complete noise rejection and the use of derivatives can enhance the noise as well. In many cases the noise occurs only on one lead and the addition of a noisy lead to the QRS enhanced signal decreases the overall detection performances of the QRS detector. For this reason the noise estimation on each channel, providing information for the channel inclusion or rejection in building the QRS enhanced signal, can improve the overall performances of the QRS detector. The results have been evaluated on the 48 records of the MIT-BIH Arrhythmia Database where each ECG record is composed by 2 leads sampled at 360 Hz for a total duration of about 30 minutes. The annotated QRSs are 109494 in total. The results have been very satisfying on all the annotated QRSs and, with the inclusion of an automatic criterion for ventricular flutter detection, a sensitivity=99.76% and a positive predictive value=99.81% have been obtained.